Exploring the effect of social media on the purchase intention of k-pop fans in Malaysia - Chiah, Wei Wei (2024)
This study explores the factors that influence purchase intentions among K-pop fans in Malaysia, with a particular emphasis on the effect of social media. As K-pop develops into a global cultural phenomenon, aesthetics, emotional ties, online community interactions, and idol endorsements influence fan purchase decisions. A quantitative survey of 60 Malaysian K-pop fans aged 18-30 revealed that visually appealing merchandise designs, idols' social media activity, and fan involvement on digital platforms all had a substantial influence on purchase decisions. Emotional connection and the desire to support idols appeared as major motivators, whereas price and perceived value had an important influence on consumer behaviour, particularly among student respondents. Despite limitations in sample size and demographic diversity, this study offers helpful details for marketers and entertainment companies looking to increase interaction with K-pop fans. Future research should incorporate a larger sample size and a more in-depth look at gender and employment disparities in fan purchase intention.